Primary systemic amyloidosis associated with multiple myeloma - Oliveira,Ederson Valei Lopes de (2012)
This case report is about a 48-year-old female patient with systemic amyloidosis and multiple myeloma simultaneously. Amyloid cutaneous infiltrative lesions like papules, nodules, or plaques with a serous-hemorrhagic aspect were found in the eyelids, neck and retroauricular region, among others. She had presented intermittent papular lesions on the upper eyelids one year before, which worsened following local trauma. A local skin biopsy showed amorphous and eosinophilic substance in the dermis. Congo red staining confirmed the amyloid deposits. Abnormal exams: proteinuria (570mg/24h), Bence-Jones proteinuria and clonal plasma cells (70%) found in myelogram. Following the diagnosis of multiple myeloma based on amyloid skin lesions, the patient was referred to the Hematology service and died 5 months after the diagnosis.